2019
DOI: 10.1021/acscentsci.8b00881
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Azolog Space Enables the Optical Control of New Biological Targets

Abstract: Photopharmacology relies on molecules that change their biological activity upon irradiation. Many of these are derived from known drugs by replacing their core with an isosteric azobenzene photoswitch (azologization). The question is how many of the known bioactive ligands could be addressed in such a way. Here, we systematically assess the space of molecules amenable to azologization from databases of bioactive molecules (DrugBank, PDB, CHEMBL) and the Cambridge Structural Database. Shape similarity scoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 35 publications
0
122
0
Order By: Relevance
“…Depending on their electronic nature and substitution pattern, they can thermally isomerize back to their trans-form in at unable fashion, with thermal half-lives ranging from nanoseconds to days under physiological conditions.A lthough several azobenzene photoswitches have been reported to be biologically active in their thermodynamically less stable cis-form, [10,[26][27][28] the majority are more active in the dark, that is,a st heir thermodynamically more stable trans-isomers.T his is,i np art, because their parent compounds tend to bind in elongated or stretched conformations,a sd emonstrated by ar ecent computational analysis of drug-like molecules that are suitable to azologization. [29] Cyclic azobenzene photoswitches,a lso known as diazocines,w herein the diazene unit is embedded in an eightmembered ring, have been known for many years but were only recently photophysically and conformationally characterized by Temps and Herges. [30][31][32][33][34] In contrast to standard azobenzenes,t heir bent cis-isomer is thermodynamically more stable and predominates in the dark, while exposure to light in the violet or deep blue range of the visible light spectrum promotes the formation of the thermodynamically less stable,e longated trans-isomer.W ep ostulated that the stable cis-isomer of the diazocine could effectively mimic the cis-isomer of as tandard azobenzene,w hereas the elongated trans-diazocine would sterically resemble the trans-isomer of as tandard azobenzene.S imilar to azobenzenes,d iazocines undergo al arge change in dipole moment upon isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their electronic nature and substitution pattern, they can thermally isomerize back to their trans-form in at unable fashion, with thermal half-lives ranging from nanoseconds to days under physiological conditions.A lthough several azobenzene photoswitches have been reported to be biologically active in their thermodynamically less stable cis-form, [10,[26][27][28] the majority are more active in the dark, that is,a st heir thermodynamically more stable trans-isomers.T his is,i np art, because their parent compounds tend to bind in elongated or stretched conformations,a sd emonstrated by ar ecent computational analysis of drug-like molecules that are suitable to azologization. [29] Cyclic azobenzene photoswitches,a lso known as diazocines,w herein the diazene unit is embedded in an eightmembered ring, have been known for many years but were only recently photophysically and conformationally characterized by Temps and Herges. [30][31][32][33][34] In contrast to standard azobenzenes,t heir bent cis-isomer is thermodynamically more stable and predominates in the dark, while exposure to light in the violet or deep blue range of the visible light spectrum promotes the formation of the thermodynamically less stable,e longated trans-isomer.W ep ostulated that the stable cis-isomer of the diazocine could effectively mimic the cis-isomer of as tandard azobenzene,w hereas the elongated trans-diazocine would sterically resemble the trans-isomer of as tandard azobenzene.S imilar to azobenzenes,d iazocines undergo al arge change in dipole moment upon isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…amide, ether, alkane or alkyne). 8 In the case of azobenzene the bridge is a diazene group (also called azo group) and depending on the wavelength of illumination, a linear trans isomer or a bent cis isomer can be obtained. 9 In this way, if a biaryl moiety is replaced by an azobenzene (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…azologization approach), there is relatively good chance that one of the resulting photoisomers will have a similar spatial disposition to the original biaryl unit and, therefore, a similar biological activity that might change upon isomerization of the 2 azobenzene. 8 The second reason for the success of azobenzene in the photopharmacology field is the robust photoisomerization. It provides typically high yields of photoisomerization with relatively low intensity of light and minimal photobleaching even over hundreds of cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that the azobenzene-containing retinoic acid receptor a (RARa) agonist Azo80 11 allows for optical control of RARa. 12 We envisioned that photoswitchable NHR modulators, termed 'photohormones', could facilitate progress in the study of NHRs. Herein, we describe the development of a photoswitchable FXR agonist, termed AzoGW.…”
mentioning
confidence: 99%
“…These results suggest reduced potency of the cis-isomer in keeping with the predictions of our chemoinformatic azologization study. 12 To explore if AzoGW allows for light-dependent activation of FXR, we carried out a luminescent reporter gene assay for human FXR, where the ligand-binding dependent activation of FXR is coupled to the expression of the reporter gene rey luciferase. We used varying concentrations of GW4064 and AzoGW (Fig.…”
mentioning
confidence: 99%